2022
DOI: 10.14309/ajg.0000000000001650
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Clinical Relapses in Pediatric Luminal Crohn's Disease: A Retrospective Cohort Study

Abstract: INTRODUCTION:There is currently little knowledge on factors associated with the relapse of Crohn's disease (CD) in children. The aims of this study were to describe the risk factors associated with relapse in pediatric CD and the changes in the relapse rate over the past decade.METHODS:Patients younger than 18 years and diagnosed between 2009 and 2019 were included in this retrospective cohort study. Clinical, endoscopic, histological, and laboratory data, as well as induction and maintenance treatments, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In summary, the quality and efficacy of treatment in pediatric IBD appear to have improved, as children with Crohn’s disease suffer fewer relapses in the last five years than 10–15 years ago [ 47 ]. Early treatment with infliximab or adalimumab should be considered if patients are at high risk of a poor outcome, e.g., Crohn’s with persistently high disease activity despite adequate induction therapy, extensive or pan-enteric manifestation, deep colonic ulcerations, marked growth retardation, severe perianal involvement, radiologically or endoscopically proven structures, the occurrence of fistulas, intestinal perforations, inflammatory conglomerates and/or abscesses, and CMV infections [ 2 ].…”
Section: Therapeutic Drug Monitoring To Optimize the Treatment Strate...mentioning
confidence: 99%
“…In summary, the quality and efficacy of treatment in pediatric IBD appear to have improved, as children with Crohn’s disease suffer fewer relapses in the last five years than 10–15 years ago [ 47 ]. Early treatment with infliximab or adalimumab should be considered if patients are at high risk of a poor outcome, e.g., Crohn’s with persistently high disease activity despite adequate induction therapy, extensive or pan-enteric manifestation, deep colonic ulcerations, marked growth retardation, severe perianal involvement, radiologically or endoscopically proven structures, the occurrence of fistulas, intestinal perforations, inflammatory conglomerates and/or abscesses, and CMV infections [ 2 ].…”
Section: Therapeutic Drug Monitoring To Optimize the Treatment Strate...mentioning
confidence: 99%
“…Multiple studies have identified risk factors for hospitalizations, surgeries, and complications from Crohn’s disease ( 45–48 ), as well as hospitalization or colectomy in ulcerative colitis ( 49 ). For example, a recent retrospective Canadian study found that female sex, 5ASA medication use, immunomodulator use (instead of anti-TNF biologics), granulomas and eosinophils on biopsies, elevated inflammatory markers during clinical remission, and lower serum infliximab titres during clinical remission were associated with clinical relapse ( 50 ). Two recent systematic reviews from the Pediatric IBD-Ahead group summarized the literature on risk prediction for children with Crohn’s disease and ulcerative colitis ( 51 , 52 ).…”
Section: Treatment Of Paediatric Ibdmentioning
confidence: 99%
“…• Un paciente es refractario al tratamiento cuando después de haber excluido la no adherencia o la presencia de otra enfermedad causante de los signos y síntomas, se presenta más de una recaída en el curso de un año, a pesar de un manejo de mantenimiento adecuado con inmunomoduladores, anti-TNF u otros biológicos, o no responde a la terapia de inducción con corticoides o con NEE (68,127,158) . • En un reciente estudio de cohorte restrospectivo, de recaída de ECP luminal, se encontró que las siguientes variables se asociaron con la recaída clínica: sexo femenino, exposición a 5-ASA oral, uso de agentes inmunomoduladores y aumento de eosinófilos en biopsias intestinales, niveles altos de PCR y CF y niveles bajos de infliximab sérico (158) . • En niños se han documentado iguales resultados de los anti-TNF que en adultos, pero en ensayos clínicos no enmascarados.…”
Section: Puntos Prácticosunclassified